Modulating the dynamics of Förster resonance energy transfer and singlet fission by variable molecular spacers. Issue 45 (12th November 2020) - Zirzlmeier, Johannes; Lavarda, Giulia; Gotfredsen, Henrik; Papadopoulos, Ilias; Chen, Lan; Clark, Timothy; Tykwinski, Rik R.; Torres, Tomás; Guldi, Dirk M.
Abstract : The synergy between panchromatic absorption and molecular singlet fission (SF) is exploited to optimize solar energy conversion. Abstract : In contrast to previous work, the synergy between panchromatic absorption and molecular singlet fission (SF) is exploited to optimize solar energy conversion through evaluation of the distance dependence of intramolecular Förster Resonance Energy Transfer (i-FRET) in a series of subphthalocyanines (SubPcs) linked to pentacene dimers (Pnc2 s). To provide control over i-FRET, the molecular spacer rather than the energy donating SubPc is tailored in the corresponding SubPc–Pnc2 conjugates in terms of length ( i.e., the number of aryl units) and flexibility ( i.e., presence or absence of a CH2 group). AM1–CIS calculations support the experiments, which underline the importance of the molecular spacer to impact not only the i-FRET dynamics, but also the dynamics of intramolecular singlet fission (i-SF). For example, an additional phenyl group slows down both i-FRET and i-SF by a factor of ∼3.8 and ∼1.6, respectively, by a quinone-like conjugation pattern that affords a pentacene acceptor orbital that is fairly delocalized over both pentacenes and the bridging phenyl.